Siglec expression on the surface of human, bull and ram sperm. Issue 4 (April 2018) - Alkhodair, K; Almhanna, H; McGetrick, J; Gedair, S; Gallagher, M E; Fernandez-Fuertes, B; Tharmalingam, T; Larsen, P B; Fitzpatrick, E; Lonergan, P; Evans, A C O; Carrington, S D; et al.
Abstract : Sialic acid (Sia) is a major constituent of both the sperm glycocalyx and female reproductive mucosal surface and is involved in regulating sperm migration, uterotubal reservoir formation and oocyte binding. Siglecs (sialic acid-binding immunoglobulin – like lectins) commonly found on immune cells, bind to Sia in a linkage- and sugar-specific manner and often mediate cell-to-cell interactions and signalling. Proteomic and transcriptomic analysis of human and bovine sperm have listed Siglecs, but to date, their presence and/or localisation on sperm has not been studied. Therefore, the aim of this study was to characterise the presence of Siglecs on the surface of bovine, human and ovine sperm using both immunostaining and Western blotting. Siglec 1, 2, 5, 6, 10 and 14 were identified and displayed both species- and regional-specific expression on sperm. Almost universal expression across Siglecs and species was evident in the sperm neck and midpiece region while variable expression among Siglecs, similar among species, was detected in the head and tail regions of the sperm. The possible role for these proteins on sperm is discussed.